Efektivitas Latihan Imajeri Mental dalam Penguasaan Lob Bertahan dalam Permainan Bulutangkis - Najah, Nur Holisotun; Hidayat, Yusuf; Nugraha, Reshandi; Hambali, Burhan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to test the effectiveness of mental imagery training in mastering defensive lob skills in badminton. The research was conducted on 14 male badminton student-athletes who participated in extracurricular activities, using a quasi-experimental method and a single-group pre-test and post-test design. Based on the analysis results, it was found that the mental imagery training method significantly influenced the mastery of the primary defensive lob skills of playing badminton. In conclusion, according to the results of this analysis, the mental imagery training method can be used as an alternative to improve mastery of defensive lob skills in badminton. Keywords: Badminton athlete, mental imagery, quantitative